AB0690 Clinical experience with infliximab biosimilar (BOW015) in ankylosing spondylitis- efficacy and safety analysis from an indian perspective. (15th June 2017) - Agrawal, I; Roy, AN; Kiran, R; Rao, VK; Sarkar, RN; Naorem, S; Ray, A; Shamil, M
Abstract : Background: The regulatory phase III trial supporting the approval of biosimilar infliximab (BOW015) in India included only rheumatoid arthritis patients. Consequently there is paucity of data on the effectiveness of BOW015 in Ankylosing Spondylitis (AS). 1, 2, 3 Hence, we decided to objectively quantify the effectiveness and safety of BOW015 in AS patients. Objectives: To determine safety, efficacy and tolerability of BOW015 in Indian AS patients. Methods: We retrospectively collected data from seven centres to get a comprehensive picture of the Indian population. The protocol along with data collection form was designed by the investigators and ethics committee approval was obtained. Biologic naïve patients diagnosed with AS as per Assessment of Spondylo Arthritis International Society criteria who were having six months of follow up data during January-November 2016 were included in the study. Percentage of patients achieving major clinical improvement (Ankylosing Spondylitis Disease Activity Score C-reactive protein (ASDASCRP >1.1 from the baseline to six months of follow up), change in ASDASCRP, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), CRP and Erythrocyte Sedimentation Rate (ESR) from the baseline to six months. Variables were reported as mean ± Standard Deviation (SD), absolute change in variable were reported along with their Confidence Interval (CI) and data was analyzed using Statistical Package for the Social Science V-22. Results: A total of 68 patients treated with BOW015 having follow-up data for six months were analyzed. Mean age of patients was 32.63±11.73 (SD) years with mean body mass index of 25.72±7.48 (SD) kg/m 2 and about 32 (47%) patients had peripheral arthritis. Of the treated patients, 52 (76%) patients were administered four doses while 6 (9%) patients administered three doses, 3 (5%) patients administered two doses and 7 (10%) patients administered single dose as they were loss to follow up. As per the primary variable, 67.9% patients achieved major clinical improvement, 9.4% patients achieved clinical improvement and 22.6% were non-responders. There was an absolute change of -2.54 (95% CI -1.92, -3.17) in BASDAI and -1.77 (95% CI -1.43, -2.11) in ASDASCRP right from first follow up corresponding to post 1st dose visit which was statistically significant (see Table-1). This trend was observed in the subsequent visits in BASDAI, ASDASCRP, ESR and CRP which continued till the end of six months. One patient developed pulmonary tuberculosis and marginally elevated liver enzymes were seen in two patients. Conclusions: BOW015 showed significant improvement in ASDASCRP and BASDAI in patients with AS on a six month follow up period and the clinical benefits were apparent as early as first dose of BOW015. References: Kay J et al. Ann Rheum Dis 2014; 73(Suppl2):64. Kay J et al. Arthritis Rheumatol. 2014; 66(12):3538. Dörner T, Kay J. Biosimilars in rheumatology: current perspectives and lessons learnt. Nat Rev Rheumatol. 2015 Dec;11(12):713–24. Disclosure of Interest: I. Agrawal: None declared, A. Roy: None declared, R. Kiran: None declared, V. Rao: None declared, R. Sarkar: None declared, S. Naorem: None declared, A. Ray: None declared, M. Shamil Employee of: Sun Pharma Laboratories Ltd, Mumbai, India